Analisis dan Mitigasi Bencana Alam Kekeringan terhadap Kebutuhan Air Baku di Perumahan Antasari Permai Sukabumi Bandar Lampung - Sandya, I Gede Agung; Zain, Alfath; Jamaludin, Jamaludin (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to carry out a drought analysis of raw water needs in these settlements, as well as designing mitigation strategies to overcome this problem. The research method involves field surveys and drought index analysis using the Standardized Precipitation Index (SPI) method. The results of analysis using the SPI-3 and SPI-12 methods show that in the last 20 years the nature of the drought index in the Antasari Permai Housing Complex has been dominated by "Normal" characteristics. The times that should receive more attention are June to November because in these months the drought shows the characteristics of "Extreme Dry" compared to other months. As a response, the proposed mitigation strategies can be implemented in the short term or long term. In the short term, mitigation is carried out by supplying clean water using water tankers, PDAM or by building rainwater reservoirs. Meanwhile, the long term is carried out in an integrated and sustainable manner by considering natural phenomena, weather anomalies, groundwater cycles. Maintaining the groundwater cycle by means of reforestation and groundwater conservation planning in the form of biopores or infiltration wells. Implementation of this strategy is expected to increase the resilience of settlements to drought and ensure the availability of adequate raw water for community needs.